If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 8 = 33 Reorder the terms: 8 + 5x = 33 Solving 8 + 5x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 5x = 33 + -8 Combine like terms: 8 + -8 = 0 0 + 5x = 33 + -8 5x = 33 + -8 Combine like terms: 33 + -8 = 25 5x = 25 Divide each side by '5'. x = 5 Simplifying x = 5
| 7x-y=30+4y | | 6x+16=13x-47 | | -8x+9y=77 | | 24+5x=4(6+2x)-3x | | (4x+3)(x+4)-(x-1)(x-3)=3x(x-2) | | 36=-19(y+8) | | -4[2x-3(3x+4)]+5x=-17 | | x-5=15*5 | | 46=-20(y+9) | | x^2-48=2x | | 106-2x=25x+22 | | 22=-11(y+7) | | 6-10x=66-24x | | 16x^5+27=0 | | 30=2(10-u) | | 6-6x=14-8x | | 4(x-5)-2(x+2)=5x-12 | | 30=3(10-y) | | (4x+3)(x-4)-(x-1)(x-3)=3x(x-2) | | -13y=-26 | | 7x^2-13x-2=0 | | x+5(x-3)=9 | | 4y+8=5y-1 | | 3x+26=11x-62 | | 5+10x=50+x | | 7x-8=6x+1 | | -13=-(3n-6)-(-6+2n) | | ax=0 | | 6y+4=7y-3 | | 5(x+2)=1 | | 6x^2-7x-3=0 | | R+25=75 |